Effects of scapular treatment on chronic neck pain: a systematic review and meta-analysis of randomized controlled trials - Yin Chen; Chunlan Yang; Kailu Nie; Jiapeng Huang; Yun Qu; Tingting Wang (BMC Musculoskeletal Disorders, 2024)
Abstract Background Chronic neck pain (CNP) is a common public health problem that affects daily living activities and quality of life. There is biomechanical interdependence between the neck and scapula. Studies have shown that shoulder blade function might be related to chronic neck pain. We therefore evaluated the effects of scapular targeted therapy on neck pain and function in patients with CNP. Methods Databases, including MEDLINE (via PubMed), EMBASE (via Ovid), Ovid, Web of Science, and Scopus, were systematically searched for randomized controlled trials published in English investigating treatment of the scapula for CNP before July 16, 2023. Results A total of 313 participants were included from 8 RCTs. Compared with those in the control group, the intervention in the scapular treatment group exhibited greater improvement in pain intensity (standardized mean difference (SMD) = 2.55; 95% CI = 0.97 to 4.13; P = 0.002), with moderate evidence. Subgroup analysis for pain intensity revealed a significant difference between the sexes, with only the female population (SMD = 6.23, 95% CI = 4.80 to 7.65) showing better outcomes than those with both sexes (SMD = 1.07, 95% CI = 0.57 to 1.56) (p < 0.00001). However, moderate evidence demonstrated no improvement in neck disability after scapular treatment (SMD of 0.24[-0.14, 0.62] of Neck Disability Index or Northwick Park Neck Pain Questionnaire). No effect of scapular treatment was shown on the pressure pain threshold (PPT). The cervical range of motion (CROM) and electromyographic activity of neck muscles could not be conclusively evaluated due to limited support in the articles, and further study was needed. However, the patient’s head forward posture appeared to be corrected after scapular treatment. Conclusion Scapular therapy was beneficial for relieving pain intensity in patients with CNP, especially in women. Head forward posture might also be corrected with scapular therapy. However, scapular therapy may have no effect on the PPT or neck disability. However, whether scapular therapy could improve CROM and cervical muscle activation in patients with CNPs had not been determined and needed further study.